2019
DOI: 10.1111/acel.12980
|View full text |Cite
|
Sign up to set email alerts
|

Advanced age promotes colonic dysfunction and gut‐derived lung infection after stroke

Abstract: Bacterial infection a leading cause of death among patients with stroke, with elderly patients often presenting with more debilitating outcomes. The findings from our retrospective study, supported by previous clinical reports, showed that increasing age is an early predictor for developing fatal infectious complications after stroke. However, exactly how and why older individuals are more susceptible to infection after stroke remains unclear. Using a mouse model of transient ischaemic stroke, we demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Stroke-induced gut barrier permeability and dysfunction precede bacterial translocation [33]. Wen and colleagues [34] showed that aging exacerbates intestinal barrier dysfunction after experimental stroke, which promotes bacterial translocation and contributes to increased lung infection in mice. Another study showed that stroke induces gut permeability and bacterial translocation in both young and aged mice, but only young mice are able to resolve these changes [35].…”
Section: Microbiota-gut-brain Axis In Acute Cerebral Ischemiamentioning
confidence: 99%
“…Stroke-induced gut barrier permeability and dysfunction precede bacterial translocation [33]. Wen and colleagues [34] showed that aging exacerbates intestinal barrier dysfunction after experimental stroke, which promotes bacterial translocation and contributes to increased lung infection in mice. Another study showed that stroke induces gut permeability and bacterial translocation in both young and aged mice, but only young mice are able to resolve these changes [35].…”
Section: Microbiota-gut-brain Axis In Acute Cerebral Ischemiamentioning
confidence: 99%
“…an important topic in the current medical field 42,43) , studies have shown that ischemic stroke can cause an increase in intestinal barrier permeability [44][45][46] . Whether in morphological observation or protein level detection, the intestinal barrier of the Model group was destroyed and the permeability was enhanced.…”
Section: Biological and Pharmaceutical Bulletin Advance Publicationmentioning
confidence: 99%
“…The results of this study showed that patients with HAP were significantly older than those without HAP (there were 352 HAP patients and 820 non-HAP patients), which suggests that age is a predictor of HAP. In addition to the well-known decline in immunity that patients may develop with age, Wen et al (27) found that the characteristics of the gut microbiota in elderly adults are very different compared to those of healthy adults, and the gut microbiota in the elderly is characterized by reduced bacterial diversity, which is associated with increased frailty, which in turn aggravates the possibility of infection in the elderly.…”
Section: Age Factormentioning
confidence: 99%